Kv2.1 negatively regulates Reissner fiber development - Amini, R. Rosa; Jain, Ruchi P.; Jędrychowska, Justyna; Korzh, Vladimir (Frontiers in Cell and Developmental Biology, 2026)
IntroductionThe potassium voltage-gated channel Kv2.1 plays a crucial role in the development of the brain’s ventricular system. Defects in the development of this system affect the formation of the Reissner fiber, a rope-like structure produced by the flexural and subcommissural organs that secrete Scospondin.MethodsThe development of the Reissner fiber has been studied during normal development and in zebrafish mutants deficient in activity of the two Kv2.1 subunits – Kcnb1 and Kcng4b using a combination of immunohistochemistry and transgenic lines expressing EGFP in the subcommissural organ and floor plate.ResultsThe Reissner fiber develops in stages. First, the midline floor plate cells, originating from the embryonic organizer, secrete Scospondin, forming the posterior Reissner fiber. This allows us to define the posterior Reissner fiber as the acellular derivative of the embryonic organizer. The fiber separates from the floor plate, beginning in the hindbrain and extends through the neural tube, from the most anterior floor plate (i.e. the flexural organ) anteriorly to the ampulla terminalis. Second, the subcommissural organ, which is derived from the anterior roof plate, begins secreting Scospondin. This forms the anterior Reissner fiber, which spans the cerebral aqueduct. Third, the anterior Reissner fiber connects to the flexural organ, where the two fibers fuse. Fourth, after the floor plate ceases to express Scospondin, the Reissner fiber derived from the subcommissural organ replaces the transient posterior fiber derived from the floor plate. Like the subcommissural organ, the flexural organ is an attachment point for the Reissner fiber. Reissner fiber assembly involves the formation of individual microfilaments that fuse in several steps to form the single fiber.DiscussionAnalysis of zebrafish mutants of Kv2.1 subunits (Kcnb1 and Kcng4b) revealed that Kv2.1 negatively regulates Scospondin production at several levels. These mutations have opposing effects on the transcript levels of several genes involved in Reissner fiber development (sspo, lgals2, and chl1a/camel), affect the subcommissural organ and microfilament formation, and impact Reissner fiber assembly.